The Effect of Building Area and Cost on the Accuracy of Cost Estimation in State Buildings - Subagijo, Djoko; Wahyudi, Imam; Kusumawati, Jujuk (Ilomata International Journal of Social Science, 2025)
Accurate cost estimation during the conceptual stage is crucial in ensuring effective budget allocation and reducing financial risks in government building projects. In Indonesia, especially Jakarta, the cost estimation process for government buildings is essential to optimize resource distribution. However, challenges persist in improving the precision of these estimations, particularly regarding how building area and construction cost impact the estimation process. This study employs multiple regression analysis to examine the relationship between the building area, construction cost, and the accuracy of conceptual cost estimations in Indonesian government building projects. The study was conducted using a sample of 100 completed projects in Jakarta. The regression analysis results reveal that both the building area and construction cost significantly negatively impact cost estimation accuracy, with a combined explanatory power of 58%. An increase in the building area and construction cost corresponds to more significant deviations in the estimated cost from the actual figures. The study highlights the need for more advanced estimation methodologies and standardized practices to improve accuracy in cost estimation. The findings offer practical recommendations to policymakers and construction professionals, suggesting ways to enhance cost estimation accuracy in the public sector, ultimately leading to better resource allocation and more successful project outcomes.